Religious Credibility under Fire Determinants of Religious Legitimacy in Postwar Bosnia and Herzegovina - Seibert, Leif-Hagen (Springer Fachmedien Wiesbaden : VS, 2018)
Leif-Hagen Seibert carries out a three-step praxeological analysis of empirical data from field studies in the research project "The ethos of religious peace builders" that allows for novel assessments of societal conjuncture (field theory), subjective meaning (habitus analysis), and the mutual 'rules of engagement' of religious practice (the religious nomos). Over the course of this three-step argument, the sociological concept of religious credibility - i.e. the determinants of religious legitimacy - gains more and more contours and facilitates the reevaluation of risks and chances in a peace process where religion is a vector for both peace and division. Contents Religion, War, and Peace Epistemological Considerations Structure, Agency, Meaning Religious Credibility in Bosnia and Herzegovina Target Groups Researchers and students in the fields of sociology, peace and conflict studies, comparative religions, political sciences, systematic theology Humanitarian and development aid workers The Author Dr. Leif-Hagen Seibert is a researcher at the Center for the interdisciplinary Research on Religion and Society (CIRRuS), Bielefeld. The core areas of his work are religion and conflict, critique of religion and ideology, sociological theories and methods.